2011
DOI: 10.1038/bmt.2011.129
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of non-compliance in autologous hematopoietic SCT patients undergoing out-patient transplants

Abstract: Non-compliance has received significant attention in medicine, yet few studies have examined its correlates in autologous hematopoietic SCT (AHSCT) patients. This study examined predictors of non-compliance in a sample of 151 AHSCT patients treated in an outpatient setting. Before AHSCT, participants completed a validated measure of mood and retrospective chart reviews were conducted to assess non-compliance during AHSCT, defined as refusal of oral hygiene, prescribed exercise programs, oral nutrition and/or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Non-compliance, driven by psychological issues, 43 limited financial resources, poor insight, or inadequate social support is often cited anecdotally as the root of these poor outcomes in transplant patients. This study lends limited support to this theory.…”
Section: Discussionmentioning
confidence: 99%
“…Non-compliance, driven by psychological issues, 43 limited financial resources, poor insight, or inadequate social support is often cited anecdotally as the root of these poor outcomes in transplant patients. This study lends limited support to this theory.…”
Section: Discussionmentioning
confidence: 99%
“…Not only are depression and fatigue distressing to patients, they are also associated with adverse outcomes. Depression is associated with nonadherence to the post‐HCT regimen, increased hospital length of stay, and greater mortality . Suicidal ideation is 13 times more likely in HCT recipients with depression than recipients without depression .…”
Section: Introductionmentioning
confidence: 99%
“…Depression is a cause for concern among HCT recipients due to its association with adverse health outcomes. For example, pre-transplant depression prospectively predicted slower white blood cell recovery in the first 3 weeks after transplant (McGregor et al, 2012), while post-transplant depression has been found to be associated with non-adherence to treatment (Mumby et al, 2011), increased hospital length of stay (Prieto et al, 2002), and greater mortality (Loberiza et al, 2002; Prieto et al, 2002). Moreover, HCT recipients with depression are 13 times more likely to report suicidal ideation as recipients without depression (Sun et al, 2013).…”
mentioning
confidence: 99%